3D numerical simulation of tsunami run-up from quickbird satellite data - Marghany, Maged (2007)
In this paper, work was carried out to simulate three-dimensional (3-D) tsunami run-up from high resolution remote sensing satellite data of QuickBird. In doing so, the tsunami wave spectra are extracted from QuickBird data using two dimensional di Fourier transform (2- DFFT). The tsunami propagation equation was then solved based on the standard Galerkin finite element approach to simulate 3-D tsunmai run-up.